Diagnoza dymensjonalna zespołu Aspergera - Korendo, Marta (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2022)
<span dir="ltr" style="left: calc(var(--scale-factor)*74.40px); top: calc(var(--scale-factor)*580.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.999112);" role="presentation">Asperger syndrome has been included in the common <span dir="ltr" style="left: calc(var(--scale-factor)*291.35px); top: calc(var(--scale-factor)*580.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.984931);" role="presentation">category of autistic disorders in <span dir="ltr" style="left: calc(var(--scale-factor)*75.25px); top: calc(var(--scale-factor)*594.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.982086);" role="presentation">current medical classifications. In spite <span dir="ltr" style="left: calc(var(--scale-factor)*230.87px); top: calc(var(--scale-factor)*594.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.980647);" role="presentation">of that, there are still some researches allowing <span dir="ltr" style="left: calc(var(--scale-factor)*66.35px); top: calc(var(--scale-factor)*62.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01148);" role="presentation">us to <span dir="ltr" style="left: calc(var(--scale-factor)*88.26px); top: calc(var(--scale-factor)*62.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01075);" role="presentation">see the differences in the structure and functioning of the brains of people with<span dir="ltr" style="left: calc(var(--scale-factor)*66.45px); top: calc(var(--scale-factor)*76.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00932);" role="presentation"> autism and Asperger syndrome. Differentiation <span dir="ltr" style="left: calc(var(--scale-factor)*259.71px); top: calc(var(--scale-factor)*76.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01105);" role="presentation">at the level of diagnosis is important <span dir="ltr" style="left: calc(var(--scale-factor)*66.33px); top: calc(var(--scale-factor)*90.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.03996);" role="presentation">because of the different educational and therapeutic needs of children with autism <span dir="ltr" style="left: calc(var(--scale-factor)*66.45px); top: calc(var(--scale-factor)*104.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.05055);" role="presentation">and <span dir="ltr" style="left: calc(var(--scale-factor)*84.48px); top: calc(var(--scale-factor)*105.55px); font-size: calc(var(--scale-factor)*8.60px); font-family: serif; transform: scaleX(0.966424);" role="presentation">AS<span dir="ltr" style="left: calc(var(--scale-factor)*95.28px); top: calc(var(--scale-factor)*104.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01731);" role="presentation">. This paper presents the concept of dimensional case assessment of children <span dir="ltr" style="left: calc(var(--scale-factor)*66.04px); top: calc(var(--scale-factor)*118.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01167);" role="presentation">with Asperger syndrome. The dimensional approach allows for viewing the disorder<span dir="ltr" style="left: calc(var(--scale-factor)*66.31px); top: calc(var(--scale-factor)*132.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01005);" role="presentation"> multidimensionally, taking into <span dir="ltr" style="left: calc(var(--scale-factor)*195.59px); top: calc(var(--scale-factor)*132.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01324);" role="presentation">account the severity <span dir="ltr" style="left: calc(var(--scale-factor)*279.47px); top: calc(var(--scale-factor)*132.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.03411);" role="presentation">of the phenomenon <span dir="ltr" style="left: calc(var(--scale-factor)*362.14px); top: calc(var(--scale-factor)*132.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.05077);" role="presentation">and in con<span dir="ltr" style="left: calc(var(--scale-factor)*66.30px); top: calc(var(--scale-factor)*146.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.03159);" role="presentation">nection <span dir="ltr" style="left: calc(var(--scale-factor)*99.67px); top: calc(var(--scale-factor)*146.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.02082);" role="presentation">with other factors, not only other disorders, which significantly reduces the <span dir="ltr" style="left: calc(var(--scale-factor)*66.36px); top: calc(var(--scale-factor)*160.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00526);" role="presentation">omission <span dir="ltr" style="left: calc(var(--scale-factor)*104.78px); top: calc(var(--scale-factor)*160.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.990122);" role="presentation">of non-prototypical cases in diagnoses and accelerates the use of therapeutic <span dir="ltr" style="left: calc(var(--scale-factor)*66.31px); top: calc(var(--scale-factor)*174.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.983263);" role="presentation">measures. It is necessary because of the low effectiveness of the diagnostic categorical <span dir="ltr" style="left: calc(var(--scale-factor)*66.45px); top: calc(var(--scale-factor)*188.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.0143);" role="presentation">approach.